Morphological ontogeny and complementary description of Neoseiulus subsolidus (Beglyarov) (Acari: Mesostigmata: Phytoseiidae) - Khaustov, Vladimir A.; Döker, Ismail; Joharchi, Omid; Khaustov, Alexander A. (Zootaxa, 2022)
The morphological ontogeny of Neoseiulus subsolidus (Beglyarov) (Acari: Mesostigmata: Phytoseiidae) was studied based on the specimens collected from Salix sp. (Salicaceae) leaves in Tyumen region and Altai Republic, Russia. All active life stages including larva, protonymph, deutonymph, adult female and male were described and illustrated. The taxonomic challenges in recognizing species in the canadensis species group are discussed.